A resin composition, and a prepreg, a laminate, a metal-clad laminate comprising the same

CN119490747BActive Publication Date: 2026-10-30GUANGDONG SHENGYI SCI TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311046299.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-18
Publication Date
2026-10-30
Estimated Expiration
2043-08-18

AI Technical Summary

Technical Problem

[0007]针对现有技术的不足,本发明的目的在于提供一种树脂组合物及包含其的预浸料、层压板、覆金属箔层压板,通过组分A特定的马来酰亚胺基改性物和组分B特定结构的苯并环丁烯树脂的设计和相互复配,解决马来酰亚胺化合物与低极性树脂相容性不足而分相的问题,进一步降低层压板和覆金属箔层压板在室温和回流焊后的翘曲大小,所述树脂组合物及包含其的层压板、覆金属箔层压板具有高玻璃化转变温度、低热膨胀系数等优异性能,能够充分高速封装基板材料的性能要求

Benefits of technology

[0122](1)本发明提供的树脂组合物中,组分A为特定的马来酰亚胺基改性物,其具有较高的耐热性、反应活性以及低的平面热膨胀系数,组分B为特定结构的苯并环丁烯树脂,具有低介电常数和低介质损耗角正切,反应活性高。通过组分A和组分B的设计和相互复配,解决马来酰亚胺化合物与低极性树脂相容性不足而分相的问题,进一步降低层压板和覆金属箔层压板在室温和回流焊后的翘曲大小,所述树脂组合物及包含其的覆金属箔层压板具有高玻璃化转变温度高、低热膨胀系数、低介电常数和低介质损耗角正切等,充分满足了高速封装基板材料的性能要求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490747B_ABST
    Figure CN119490747B_ABST
Patent Text Reader

Abstract

The present application provides a resin composition and prepreg, laminate, metal-clad laminate comprising the same, the resin composition comprises, in parts by mass: component A 20-90 parts, component B 5-60 parts; the component A comprises an addition reaction product of a maleimide compound a1 containing at least 2 N-substituted maleimide groups in one molecule and an amine compound a2 containing at least 2 primary amino groups in one molecule; the component B is a benzocyclobutene resin. The present application solves the problem of phase separation of maleimide compounds and low-polarity resins due to insufficient compatibility by designing and matching component A and component B, further reduces the warpage size of laminate and metal-clad laminate after room temperature and reflow soldering, the resin composition and laminate and metal-clad laminate comprising the same have excellent properties such as high glass transition temperature and low thermal expansion coefficient, fully meet the performance requirements of high-speed packaging substrate materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of printed circuit board technology, specifically relating to a resin composition and a prepreg containing the same, a laminate, and a metal foil-coated laminate. Background Technology

[0002] In recent years, communication technology has entered an era of high-speed signals and high-frequency transmission. The demand for data processing and transmission in communication technology is constantly increasing, thus placing higher requirements on the dielectric properties of related electronic materials to minimize high-frequency signal loss and delay. With the advent of the 5G era, applications such as high-frequency RF (e.g., PA, WiGig, WiHD / 60GHz), large-size chips, and DDR5 (3.2-6.4Gbps) have placed multifaceted performance requirements on substrate materials, namely, the simultaneous possession of: low planar thermal expansion coefficient, low dielectric loss tangent, low dielectric constant, higher reliability, and higher heat resistance.

[0003] To meet the performance requirements of high-frequency and high-speed electronic materials, the industry has been researching resins with good dielectric properties, including thermosetting polyphenylene ether resins, bismaleimide resins, and hydrocarbon resins. Currently, composite resin materials containing terminal alkenyl thermosetting polyphenylene ether resins and triallyl isocyanate (TAIC) have been used in the mass production of printed circuit boards (PCBs). This substrate exhibits good performance in terms of mechanical properties and heat resistance, but its dielectric constant and dielectric loss tangent are still relatively high, making it difficult to meet the requirements of next-generation communication technologies.

[0004] Bismaleimide resin is characterized by high monomer activity, high glass transition temperature, good heat resistance, stable finished product performance, and high physical and mechanical properties over a wide temperature range. For example, CN109825081A discloses a thermosetting resin composition comprising the following components: a combination of bismaleimide resin and benzoxazine resin or a prepolymer of bismaleimide resin and benzoxazine resin, epoxy resin, and reactive ester; the metal-coated foil laminate prepared by this resin composition has a high glass transition temperature, low coefficient of thermal expansion, high high temperature modulus, and good heat resistance; however, the cured bismaleimide resin is brittle, has a short shelf life, low dielectric loss tangent, and its dielectric properties still have considerable room for improvement.

[0005] Hydrocarbon resins exhibit excellent toughness and dielectric properties, and are often used in combination with other thermosetting resins to reduce the dielectric loss tangent and dielectric constant of the material. For example, CN114437435A discloses a hydrocarbon resin-based prepreg comprising a reinforcing fabric core and an outer hydrocarbon resin layer. The hydrocarbon resin layer comprises: 20-40 parts hydrocarbon resin, 10-20 parts bismaleimide resin, 5-10 parts benzoxazine, 5-10 parts thermally conductive filler, and 1-5 parts curing agent. High-frequency copper-clad laminates prepared using this hydrocarbon resin-based prepreg exhibit good dielectric properties. However, hydrocarbon resin materials generally have insufficient heat resistance and a large coefficient of thermal expansion, making it difficult to meet the performance requirements of high-speed packaging substrates.

[0006] Therefore, developing a prepreg, laminate, or metal foil laminate with excellent dielectric properties, low coefficient of thermal expansion, and high heat resistance, while exhibiting low warpage during use and meeting packaging reliability requirements, is a key research focus in this field. Summary of the Invention

[0007] To address the shortcomings of existing technologies, the present invention aims to provide a resin composition and prepregs, laminates, and metal foil laminates containing the same. By designing and compounding a specific maleimide-based modifier in component A and a benzocyclobutene resin with a specific structure in component B, the problem of phase separation due to insufficient compatibility between maleimide compounds and low-polarity resins is solved. This further reduces the warpage of the laminates and metal foil laminates at room temperature and after reflow soldering. The resin composition and the laminates and metal foil laminates containing the same possess excellent properties such as high glass transition temperature and low coefficient of thermal expansion, which can fully meet the performance requirements of high-speed encapsulation substrate materials.

[0008] To achieve this objective, the present invention adopts the following technical solution:

[0009] In a first aspect, the present invention provides a resin composition comprising, by weight, the following components:

[0010] Component A 20-90 parts

[0011] Component B: 5-60 parts.

[0012] The component A includes an addition reaction product of a maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and an amine compound a2 containing at least two primary amino groups in one molecule.

[0013] Component B is a benzocyclobutene resin, which contains at least one first structural unit and at least one second structural unit.

[0014] The first structural unit has a structure as shown in at least one of formulas IA, IB, and IC:

[0015]

[0016] In formula IC, R1 is vinylidene or ethylidene.

[0017] The second structural unit has the structure shown in Equation II:

[0018]

[0019] In Formula II, R2 is vinyl, ethyl, or phenyl.

[0020] The resin composition provided by this invention contains a combination of component A and component B in specific mass parts. The structural and property characteristics of the two components are as follows:

[0021] Component A: A specific maleimide-modified compound, comprising an addition reaction product of a maleimide compound a1 containing at least two (e.g., two, three, or four) N-substituted maleimide groups in one molecule and an amine compound a2 containing at least two (e.g., two, three, four, or five) primary amino groups in one molecule. Component A is a mixture of maleimides, including maleimide addition reaction monomers, maleimide addition reaction oligomers or polymers, and maleimide monomers, maleimide oligomers or polymers that have not participated in the addition reaction. Component A contains primary amino, secondary amino, and carbon-carbon double bonds, exhibiting high reactivity. After curing, Component A exhibits high heat resistance and a low coefficient of planar thermal expansion.

[0022] Component B: A benzocyclobutene resin with a specific structure, wherein the side chain of the first structural unit contains a benzocyclobutyl structure, and the second structural unit is any one or a combination of at least two of the following: a polybutadiene structure, a hydrogenated polybutadiene structure, and a polystyrene structure. The benzocyclobutene resin has an all-carbon structure, exhibiting a low dielectric constant and a low dielectric loss tangent. Simultaneously, the molecular structure of the benzocyclobutene resin contains readily reactive alkenyl groups (alkenyl groups derived from the polybutadiene structure, thermally ring-opening to form C=C benzocyclobutene rings), allowing for better dielectric properties through thermosetting. Furthermore, the resin structure contains multiple benzocyclobutene functional groups, enabling self-crosslinking to achieve a high crosslinking density, thus improving the shortcomings of butadiene-based hydrocarbon resins, such as low glass transition temperature, high coefficient of thermal expansion, and insufficient rigidity. This makes it highly suitable for use as a packaging substrate material with requirements for both thermal expansion coefficient and rigidity.

[0023] This invention improves the compatibility of resin compositions by designing and compounding components A and B. The resin composition in the clear varnish state is homogeneous and does not exhibit stratification or precipitation after standing. Prepregs, laminates, and metal foil-coated laminates do not experience phase separation or resin aggregation, exhibiting excellent process performance. Simultaneously, components A and B contain numerous reaction sites and high reactivity, and each can self-polymerize at suitable temperatures, significantly increasing the crosslinking density of the resin composition. The cured product possesses a high glass transition temperature, low coefficient of thermal expansion, and excellent heat resistance, mitigating the performance degradation problems caused by insufficient crosslinking density in butadiene-based hydrocarbon resins (such as increased warpage due to high coefficient of thermal expansion and insufficient rigidity). The resin composition and the metal foil-coated laminate containing it have low dielectric constant Dk and low dielectric loss tangent Df, exhibiting excellent dielectric properties and fully meeting the performance requirements of high-speed packaging substrate materials.

[0024] In the resin composition provided by the present invention, the mass part of component A is 20-90 parts, for example, it can be 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts or 85 parts, as well as specific values ​​between the above points. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range. Preferably, it is 30-90 parts, and more preferably 40-70 parts.

[0025] The "parts" and "parts by weight" used in this invention are calculated based on solid content and do not include solvents, dispersants, etc.

[0026] The component B is 5-60 parts by mass, for example, 5, 8, 10, 15, 20, 25, 30, 35, 40, 45, 50 or 55 parts, and specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range, but preferably 5-40 parts.

[0027] In the resin composition provided by the present invention, component A and component B are combined and compounded in a specific ratio, which endows the resin composition, prepreg, laminate and metal foil laminate with high glass transition temperature, low planar thermal expansion coefficient and excellent heat resistance, and the cured product has excellent warpage performance.

[0028] In the resin composition provided by this invention, if the amount of component A is too low, the glass transition temperature of the resin composition will be low, the coefficient of thermal expansion will be high, the heat resistance will be low, and the resistance to deformation, especially at high temperatures, will be poor, leading to severe warping and affecting the reliability of the encapsulation. If the amount of component A is too high, the dielectric loss of the resin composition will be high and the dielectric properties will be low. If the amount of component B is too low, the dielectric loss of the resin composition will be high. If the amount of component B is too high, the heat resistance of the resin composition will decrease, the coefficient of thermal expansion will increase, and the resistance to deformation will be poor.

[0029] Preferably, the molar percentage of the first structural unit in the benzocyclobutene resin is ≥5%, for example, it can be 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, or 80%, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range. More preferably, it is ≥30%, and even more preferably, it is 30-60%.

[0030] Preferably, the molar percentage of the second structural unit in the benzocyclobutene resin is 15-90%, for example, it can be 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or 85%, and specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0031] As a preferred embodiment of the present invention, in the benzocyclobutene resin, the molar percentage of the first structural unit containing benzocyclobutene groups in the side chain is 5-80%, more preferably 30-60%, and the molar percentage of the second structural unit is 15-90%, more preferably 30-70%. This gives the benzocyclobutene resin both excellent reactivity and dielectric properties. Therefore, when combined with other resins, it can improve the thermosetting crosslinking reactivity and crosslinking density, thereby enhancing the heat resistance and mechanical properties of the resin composition. If the molar percentage of the first structural unit is too low, the crosslinking density of the benzocyclobutene resin itself will decrease, thus affecting the glass transition temperature and coefficient of thermal expansion of the resin composition. If the molar percentage of the first structural unit is too high, on the one hand, it will increase the difficulty of synthesizing the benzocyclobutene resin and the production cost; on the other hand, it will leave a large number of unreacted benzocyclobutene groups in the resin composition. During subsequent use of the cured product, the remaining benzocyclobutene groups will further react, generating a large amount of stress, affecting the warpage performance of the resin composition, the laminate, and the metal foil-coated laminate.

[0032] Preferably, the benzocyclobutene resin further comprises a third structural unit having a structure as shown in Formula IIIA and / or Formula IIIB:

[0033]

[0034] It should be noted that the benzocyclobutene resin has a polymer segment structure, including at least one (preferably multiple) first structural unit, at least one (preferably multiple) second structural unit, and optionally a third structural unit; the present invention does not limit the connection order of the above structural units, and any connection order / connection method feasible in chemistry is within the scope of the present invention.

[0035] Preferably, the molar percentage of the third structural unit in the benzocyclobutene resin is ≤40%, for example, it can be 0, 1%, 3%, 5%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, or 40%, or specific values ​​between the above values. For space limitations and for the sake of brevity, this invention will not exhaustively list all the specific values ​​included in the range. More preferably, it is ≤30%, even more preferably ≤20%, and most preferably ≤10%. This increases the degree of curing of the benzocyclobutene resin and the resin composition containing it, resulting in a higher glass transition temperature, a lower coefficient of thermal expansion, etc.

[0036] It should be noted that the benzocyclobutene resin of the present invention can be divided into two categories according to the type of the first structural unit: type A benzocyclobutene resin and type B benzocyclobutene resin; the component B (benzocyclobutene resin) includes type A benzocyclobutene resin and / or type B benzocyclobutene resin. The first structural unit of the type A benzocyclobutene resin has the structure shown in formula IA and / or formula IB, and the first structural unit of the type B benzocyclobutene resin has the structure shown in formula IC.

[0037] Preferably, the mass percentage content of the first structural unit (structure shown in formula IA and / or formula IB) in the type A benzocyclobutene resin is ≥10%, for example, it can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or 85%, and specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range. Preferably, it is ≥30%, and more preferably 30-80%.

[0038] For example, the preparation method of the type A benzocyclobutene resin includes: butadiene-based polymer and benzocyclobutene monomer. The reaction is carried out to obtain the type A benzocyclobutene resin; the butadiene-based polymer is polybutadiene or butadiene-styrene copolymer, wherein it contains butadiene 1,2-polymerized structural units.

[0039] Preferably, the reaction is carried out in the presence of an organic peroxide.

[0040] Preferably, the organic peroxide comprises any one or a combination of at least two of the following: tert-butylisopropylphenyl peroxide, dicumyl peroxide, benzoyl peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexyne, and 1,1-bis(tert-butylperoxy)-3,3,5-dimethylcyclohexane.

[0041] Preferably, the reaction temperature is 80-130℃, for example, it can be 85℃, 90℃, 95℃, 100℃, 105℃, 110℃, 115℃, 120℃ or 125℃, as well as specific values ​​between the above points. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0042] Preferably, the reaction time is 4-16 hours, for example, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours or 15 hours, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific values ​​included in the range.

[0043] Based on the preparation method of the aforementioned type A benzocyclobutene resin, the butadiene-1,2-polymerized structural unit in the butadiene-based polymer... It may self-polymerize in the presence of organic peroxides, thereby allowing the type A benzocyclobutene resin to further comprise a fourth structural unit, which is a polybutadiene structural unit. A structural unit with a ring-like structure formed by polymerization.

[0044] For example, the preparation method of the type B benzocyclobutene resin includes: butadiene-based polymer and 4-halogenated benzocyclobutene. A coupling reaction is performed to obtain the type B benzocyclobutene resin; the butadiene-based polymer is polybutadiene or butadiene-styrene copolymer, containing 1,2 polymeric structural units. Hal is a halogen, such as Cl, Br, or I.

[0045] Preferably, the coupling reaction is carried out in the presence of a palladium catalytic system.

[0046] Preferably, the palladium catalytic system comprises a palladium catalyst and an organophosphorus ligand.

[0047] Preferably, the palladium catalyst is palladium acetate, and the organophosphorus ligand is tris(o-methylphenyl)phosphine.

[0048] Preferably, the coupling reaction is carried out in the presence of an acid-binding agent.

[0049] Preferably, the acid-binding agent comprises an organic base, and more preferably triethylamine.

[0050] Preferably, the coupling reaction is carried out in an inert protective atmosphere, which includes any one of a nitrogen atmosphere, an argon atmosphere, and a helium atmosphere.

[0051] Preferably, the temperature of the coupling reaction is 60-100℃, for example, it can be 65℃, 70℃, 75℃, 80℃, 85℃, 90℃ or 95℃, as well as specific values ​​between the above points. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0052] Preferably, the coupling reaction time is 5-36 hours, for example, 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 24 hours, 28 hours, 32 hours or 34 hours, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific values ​​included in the range.

[0053] Preferably, the preparation of the type A benzocyclobutene resin and the type B benzocyclobutene resin each independently includes an optional hydrogenation reaction step. The hydrogenation reaction can be carried out before and / or after the aforementioned reactions. The hydrogenation reaction can be complete hydrogenation (i.e., hydrogenation of all C=C bonds in the main chain and branches of the type A benzocyclobutene resin and the type B benzocyclobutene resin, preferably carried out after the reaction) or partial hydrogenation (can be carried out before or after the reaction). The hydrogenation reaction hydrogenates all or part of the C=C double bonds from the butadiene-based polymer (polybutadiene and / or styrene-butadiene copolymer), forming saturated carbon chains; thereby, it contributes to further optimization of the dielectric properties of the benzocyclobutene resin.

[0054] Preferably, the number average molecular weight of the benzocyclobutene resin is 1,000-200,000, for example, it can be 2,000, 5,000, 8,000, 10,000, 12,000, 15,000, 20,000, 50,000, 80,000, 100,000, 120,000, 150,000, or 180,000, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0055] Preferably, the number average molecular weight of the type A benzocyclobutene resin is 1,000-200,000, for example, it can be 2,000, 5,000, 8,000, 10,000, 12,000, 15,000, 20,000, 50,000, 80,000, 100,000, 120,000, 150,000, or 180,000, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0056] Preferably, the number average molecular weight of the type B benzocyclobutene resin is 1000-20000, for example, it can be 2000, 5000, 8000, 10000, 12000, 15000 or 18000, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0057] Preferably, the maleimide compound a1 contains two N-substituted maleimide groups in one molecule.

[0058] Preferably, the maleimide compound a1 includes N,N'-ethylidene bismaleimide, N,N'-hexamethylene bismaleimide, N,N'-(1,3-phenylene)bismaleimide, N,N'-(1,3-(2-methylphenylene))bismaleimide, N,N'-(1,3-(4-methylphenylene))bismaleimide, N,N'-(1,4-phenylene)bismaleimide, bis(4-maleimide-phenyl)methane, bis(3-methyl-4-maleimide-phenyl)methane, bis(3,5-dimethyl-4-maleimide-phenyl)methane, and bis(3-ethyl-5-methyl-4-maleimide-phenyl) Methane, bis(3-ethyl-4-maleimide-phenyl)methane, bis(3,5-diethyl-4-maleimide-phenyl)methane, bis(4-maleimide-phenyl) ether, bis(4-maleimide-phenyl) ketone, bis(4-maleimide-cyclohexyl)methane, 1,4-bis(4-maleimide-phenyl)cyclohexane, 1,4-bis(maleimide-methyl)cyclohexane, 1,4-bis(maleimide-methyl)benzene, 1,3-bis(4-maleimide-phenoxy)benzene, 1,3-bis(3-maleimide-phenoxy)benzene, bis(4-(3-maleimide-phenoxy)phenyl)methane, bis(4-(4-maleimide-phenyl) 1,1-bis(4-(3-maleiminophenoxy)phenyl)ethane, 1,1-bis(4-(4-maleiminophenoxy)phenyl)ethane, 1,2-bis(4-(3-maleiminophenoxy)phenyl)ethane, 1,2-bis(4-(4-maleiminophenoxy)phenyl)ethane, 2,2-bis(4-(3-maleiminophenoxy)phenyl)propane, 2,2-bis(4-(4-maleiminophenoxy)phenyl)propane, 2,2-bis(4-(3-maleiminophenoxy)phenyl)butane, 2,2-bis(4-(4-maleiminophenoxy)phenyl)butane, 4,4' -A combination of any one or at least two of bis(3-maleiminophenoxy)biphenyl, 4,4'-bis(4-maleiminophenoxy)biphenyl, bis(4-(3-maleiminophenoxy)phenyl)one, bis(4-(4-maleiminophenoxy)phenyl)one, bis(4-(3-maleiminophenoxy)phenyl)ether, and bis(4-(4-maleiminophenoxy)phenyl)ether, further preferably any one or at least two of bis(3-ethyl-5-methyl-4-maleiminophenyl)methane, bis(4-maleiminophenyl)methane, and 2,2-bis(4-(4-maleiminophenoxy)phenyl)propane.

[0059] Preferably, the amine compound a2 comprises a siloxane compound containing at least two primary amino groups, diaminobenzidine, 3,3'-dimethoxy-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminobiphenyl, 3,3'-diethyl-4,4'-diaminobiphenyl, diaminodiphenylmethane, 3,3'-dimethoxy-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-diethyl-4,4'-diaminodiphenylmethane, and 3,3'-diethyl-4,4'-diaminodiphenylmethane. 4'-Diaminodiphenylmethane, 3,3'-Diethyl-5,5'-Diethyl-4,4'-Diaminodiphenylmethane, 3,3'-Dimethyl-5,5'-Diethyl-4,4'-Diaminodiphenylmethane, diaminodiphenyl ether, 3,3'-Dimethoxy-4,4'-Diaminodiphenyl ether, 3,3'-Dimethyl-4,4'-Diaminodiphenyl ether, 3,3'-Dimethyl-5,5'-Dimethyl-4,4'-Diaminodiphenyl ether, 3,3'-Diethyl-4,4'-Diaminodiphenyl ether, 3,3'-Diethyl-5,5'-Diethyl 4,4'-diaminodiphenyl ether, 3,3'-dimethyl-5,5'-diethyl-4,4'-diaminodiphenyl ether, 1,3-bis(4-aminophenoxy)benzene, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 2,2-bis(4-(3-aminophenoxy)phenyl)propane, 4,4'-bis(4-aminophenoxy)biphenyl, 1,4-bis(4-aminophenoxy)benzene, 2,2'-dimethyl-4,4'-diaminobiphenyl, 4,4'-diamino-3,3'-dihydroxybiphenyl; further The preferred step involves any one or a combination of at least two of the following: a siloxane compound containing at least two primary amino groups; 3,3'-dimethyl-4,4'-diaminodiphenylmethane; 3,3'-dimethyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane; 3,3'-diethyl-4,4'-diaminodiphenylmethane; 3,3'-diethyl-5,5'-diethyl-4,4'-diaminodiphenylmethane; 3,3'-dimethyl-5,5'-diethyl-4,4'-diaminodiphenylmethane; and 2,2-bis(4-(4-aminophenoxy)phenyl)propane.

[0060] As a preferred embodiment of the present invention, the amine compound a2 comprises a siloxane compound containing two primary amino groups, which can yield a resin composition with a low coefficient of planar expansion.

[0061] Exemplary examples include commercially available siloxane compounds containing two primary amino groups, such as, but not limited to, PAM-E (side-chain methyl type, functional group equivalent 130 g / mol), KF-8010 (side-chain methyl type, functional group equivalent 430 g / mol), X-22-161A (side-chain methyl type, functional group equivalent 800 g / mol), and X-22-161B (side-chain methyl type, functional group equivalent 800 g / mol) from Shin-Etsu Chemical Industry Co., Ltd. The functional group equivalent is 1500 g / mol), KF-8012 (side chain methyl type, functional group equivalent 2200 g / mol), KF-8008 (side chain methyl type, functional group equivalent 5700 g / mol), X-22-9409 (side chain phenyl type, functional group equivalent 670 g / mol), and X-22-1660B-3 (side chain phenyl type, functional group equivalent 2200 g / mol).

[0062] Preferably, in component A, the addition reaction of maleimide compound a1, which contains at least two N-substituted maleimide groups in one molecule, and amine compound a2, which contains at least two primary amino groups in one molecule, is carried out in an organic solvent; the type of organic solvent is not particularly limited, but is more preferably propylene glycol monomethyl ether.

[0063] In this invention, the addition reaction temperature of maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and amine compound a2 containing at least two primary amino groups in one molecule is not particularly limited, as long as maleimide compound a1 and amine compound a2 react. As a preferred technical solution of this invention, from the perspective of reaction rate and solvent boiling point, the temperature of the addition reaction is preferably 100-130℃, for example, 102℃, 105℃, 108℃, 110℃, 112℃, 115℃, 118℃, 120℃, 122℃, 125℃ or 128℃, and specific values ​​between the above points. Due to space limitations and for the sake of brevity, this invention will not exhaustively list the specific values ​​included in the range.

[0064] In this invention, the addition reaction time of maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and amine compound a2 containing at least two primary amino groups in one molecule is not particularly limited. Preferably, the addition reaction time is 2-10 h, for example, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h, 6 h, 6.5 h, 7 h, 7.5 h, 8 h, 8.5 h, 9 h, 9.5 h, and specific values ​​between the above values. Due to space limitations and for the sake of brevity, this invention will not exhaustively list the specific values ​​included in the range. More preferably, it is 3-8 h.

[0065] Preferably, the resin composition further includes 1-50 parts of component C by weight. For example, component C can be 2 parts, 5 parts, 8 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, or 45 parts, as well as specific values ​​between the above-mentioned values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0066] Component C includes any one or a combination of at least two of the following: epoxy resin, acid anhydride compound, active ester compound, and compound having carbon-carbon unsaturated double bonds in the molecule, preferably a compound having carbon-carbon unsaturated double bonds in the molecule.

[0067] Preferably, the compound having carbon-carbon unsaturated double bonds within its molecule includes any one or a combination of at least two of the following: unsaturated polyphenylene ether, polyfunctional vinyl compounds, allyl compounds, acrylate compounds, acenaphthene compounds, and polybutadiene.

[0068] Preferably, the unsaturated polyphenylene ether comprises polyphenylene ethers with unsaturated groups at the end; wherein the unsaturated groups can be any one or a combination of at least two of vinylbenzyl, vinylphenyl, acrylate, and methacrylate groups.

[0069] As a preferred embodiment of the present invention, in the resin composition, from the perspective of achieving a high glass transition temperature and a low coefficient of planar thermal expansion of the cured product, with a total mass of 100 parts of component A, component B and optional component C, component A is 20-90 parts, for example 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts or 85 parts, and specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range, but preferably 30-90 parts, and more preferably 40-70 parts.

[0070] As a preferred embodiment of the present invention, in the resin composition, from the perspective of achieving a low dielectric loss factor of the cured product, with a total mass of 100 parts of component A, component B and optionally component C, component B is 5-60 parts, for example, 5 parts, 8 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts or 55 parts, and specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range, but preferably 5-40 parts.

[0071] Preferably, the resin composition further comprises 5-30 parts by weight of a thermoplastic polymer, wherein the thermoplastic polymer may be 8 parts, 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts or 28 parts, and specific values ​​between the above-mentioned values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0072] Preferably, the thermoplastic polymer includes any one or a combination of at least two of styrene-based polymers, hydrogenated styrene-based polymers, and polyolefin resins.

[0073] Preferably, the styrene-based polymer is a copolymer comprising olefin structural units and styrene structural units. The olefin structural units are derived from olefin monomers, such as structural units derived from butadiene or isoprene; the styrene structural units are derived from styrene monomers, such as structural units derived from styrene or structural units derived from styrene with substituents. In addition to containing structural units derived from olefins and styrene, the styrene-based polymer may also contain structural units other than those derived from olefins and styrene, such as structural units derived from epoxy groups, amino groups, or maleic anhydride.

[0074] The styrene-based polymer can be a random copolymer or a block copolymer.

[0075] The hydrogenated styrene polymer is obtained by partially or completely hydrogenating the structural units of olefins derived from the aforementioned styrene polymer.

[0076] The styrene-based polymers and hydrogenated styrene-based polymers may be commercially available products, including but not limited to: any one or a combination of at least two of the following: Ricon 100 (butadiene-styrene copolymer, Cray Valley), Ricon 181 (butadiene-styrene copolymer, Cray Valley), Tuftec H1051 (hydrogenated styrene-butadiene copolymer with a styrene content of 42% by mass, Asahi Kasei Chemicals Co., Ltd.), and Tuftec M1913 (hydrogenated styrene-butadiene copolymer with maleic anhydride structural units, with a styrene content of 30% by mass, Asahi Kasei Chemicals Co., Ltd.).

[0077] Preferably, the resin composition further comprises 0.01-5 parts by weight of a curing accelerator, wherein the curing accelerator may be 0.02 parts, 0.05 parts, 0.08 parts, 0.1 parts, 0.3 parts, 0.5 parts, 0.8 parts, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, or 4.8 parts, as well as specific values ​​between the above-mentioned values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0078] Preferably, the curing accelerator includes any one or a combination of at least two of the following: acidic curing accelerators, organophosphorus curing accelerators, imidazole curing accelerators, pyridine curing accelerators, amine curing accelerators, peroxides, and organometallic salts.

[0079] Exemplary examples include acidic curing accelerators such as p-toluenesulfonic acid; organophosphorus curing accelerators such as triphenylphosphine; imidazole curing accelerators such as imidazole and / or imidazole derivatives (e.g., 2-methylimidazolium, 2-ethylimidazolium, or 2-ethyl-4-methylimidazolium); pyridine curing accelerators such as pyridine and / or pyridine derivatives (e.g., 4-dimethylaminopyridine); amine curing accelerators such as secondary amine compounds, tertiary amine compounds, or quaternary ammonium salts; peroxides such as dicumyl peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexyn-3, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, or α,α'-bis(tert-butylperoxy)dicumyl peroxide; and organometallic salts such as zinc naphthenate, cobalt naphthenate, tin octoate, or cobalt octoate. The curing accelerators can be used alone or in combination of at least two.

[0080] Preferably, the resin composition further comprises 5-250 parts by weight of inorganic filler, wherein the inorganic filler may be 8 parts, 10 parts, 20 parts, 30 parts, 50 parts, 70 parts, 90 parts, 100 parts, 110 parts, 130 parts, 150 parts, 170 parts, 190 parts, 200 parts, 210 parts, or 230 parts, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0081] As a preferred embodiment of the present invention, the inorganic filler helps to improve the heat resistance, damp heat resistance, and mechanical properties of the resin composition, and reduces the coefficient of thermal expansion. However, excessive use of the inorganic filler can lead to an increase in the dielectric loss tangent of the resin composition, which is detrimental to signal transmission.

[0082] This invention does not particularly limit the type of inorganic filler, but exemplary examples include, but are not limited to, any one or a combination of at least two of the following: silica, aluminum hydroxide, magnesium hydroxide, boehmite, molybdenum oxide, zinc oxide, zinc molybdate, zinc borate, zinc stannate, titanium dioxide, strontium titanate, barium titanate, barium sulfate, clay, kaolin, talc, mica, boron nitride, aluminum nitride, silicon carbide, alumina, composite silica powder, glass powder, short glass fiber, and hollow glass. To improve the heat resistance, damp heat resistance, and dimensional stability of the resin composition, it is preferred to use any one or a combination of at least two of the following: silica, aluminum hydroxide, magnesium hydroxide, boehmite, boron nitride, aluminum nitride, silicon carbide, alumina, composite silica powder, glass powder, short glass fiber, and hollow glass. The silica can be any one or a combination of at least two of the following: crystalline silica, fused silica, amorphous silica, spherical silica, and hollow silica, and is more preferably spherical silica.

[0083] The average particle size (D) of inorganic fillers 50 There are no specific limitations, but from the perspective of dispersibility, the average particle size (D) 50 The preferred particle size distribution (PPD) is 0.01-20 μm, for example, it can be 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 3 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, or 18 μm, as well as specific values ​​between the above values. For space limitations and for the sake of brevity, this invention will not exhaustively list all the specific values ​​included in the range, but 0.01-10 μm is further preferred. Different types of inorganic fillers with different particle size distributions or different average particle sizes can be used alone or in combination as needed.

[0084] For example, the particle size of the inorganic filler was obtained using an MS3000 Malvern laser particle size analyzer.

[0085] Preferably, the inorganic filler includes a surface-treated filler, and the surface treatment agent includes any one or a combination of at least two of silane coupling agents, organosilicon oligomers, and titanate coupling agents, with silane coupling agents being more preferred.

[0086] Preferably, the resin composition further comprises 0.01-10 parts by weight of coupling agent, wherein the coupling agent may be 0.05 parts, 0.1 parts, 0.5 parts, 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts or 9 parts, as well as specific values ​​between the above-mentioned values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0087] Preferably, the coupling agent comprises a silane coupling agent.

[0088] This invention does not specifically limit the type of silane coupling agent, but includes, by way of example, any one or a combination of at least two of the following: epoxy silane coupling agents, amino silane coupling agents, vinyl silane coupling agents, styryl silane coupling agents, isobutylene silane coupling agents, propylene silane coupling agents, urea silane coupling agents, mercapto silane coupling agents, chloropropyl silane coupling agents, sulfur-based silane coupling agents, and isocyanate-based silane coupling agents.

[0089] Preferably, the resin composition further includes a flame retardant. There is no particular limitation on the flame retardant, which may be selected from halogenated or non-halogenated flame retardants that are soluble or insoluble in organic solvents. Exemplarily, the non-halogenated flame retardant includes inorganic phosphorus flame retardants, organophosphorus flame retardants, metal hydrates, etc.

[0090] From the perspectives of environmental protection and excellent dielectric properties, flame retardants are preferably organophosphorus flame retardants. For example, the organophosphorus flame retardants include aromatic phosphates, monosubstituted phosphonate diesters, disubstituted hypophosphite esters, metal salts of disubstituted hypophosphite acids, organic nitrogen- and phosphorus-containing compounds, cyclic organophosphorus compounds, etc.

[0091] For example, the aromatic phosphate esters include triphenyl phosphate, tricresyl phosphate, tri(xyl) phosphate, toluene diphenyl phosphate, toluene di-2,6-xylene phosphate, resorcinol bis(diphenyl phosphate), 1,3-phenylene bis(di(2,6-dimethylphenyl) phosphate), 4,4'-biphenyl bis(di(2,6-dimethylphenyl) phosphate), bisphenol A-bis(di(2,6-dimethylphenyl) phosphate), bisphenol A-bis(diphenyl phosphate), 1,3-phenylene bis(diphenyl phosphate), etc.; the monosubstituted phosphonic acid diesters include divinyl phenylphosphonate, diallyl phenylphosphonate, bis(1-butenyl) phenylphosphonate, etc.; the disubstituted hypophosphonates include Diphenylphosphine ester, methyl diphenylphosphine ester, etc.; the metal salts of the disubstituted phosphine acids include metal salts of dialkylphosphine acids, metal salts of diallylphosphine acids, metal salts of divinylphosphine acids, metal salts of diarylphosphine acids, metal salts of diarylphosphine acids, etc.; the organic nitrogen-phosphorus compounds include phosphazene compounds, melamine phosphate, melamine polyphosphate, melamine pyrophosphate, etc.; the cyclic organophosphorus compounds include 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-phenyl-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, etc. Flame retardants can be used alone or in combination of at least two.

[0092] Solvents may also be added to the resin composition. The amount of solvent added is selected by those skilled in the art based on experience and process requirements, so that the resin composition reaches a suitable viscosity for use, facilitating coating, impregnation, and processing. During subsequent drying, semi-curing, or complete curing stages, the solvent in the resin composition will partially or completely evaporate.

[0093] The solvent used in this invention is not particularly limited, and generally can be ketones such as acetone, butanone, and cyclohexanone; aromatic hydrocarbons such as toluene and xylene; esters such as ethyl acetate and butyl acetate; alcohols such as methanol, ethanol, or butanol; alcohols such as ethyl cellosolve, butyl cellosolve, ethylene glycol monomethyl ether, carbitol, or butyl carbitol; and nitrogen-containing solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, or N-methyl-2-pyrrolidone. The solvent can be used alone or in mixtures of two or more. Preferably, ketones such as acetone, butanone, and cyclohexanone, and aromatic hydrocarbons such as toluene and xylene are used.

[0094] The resin composition provided by the present invention is prepared by the following method, the preparation method comprising: mixing and dispersing the components in the resin composition evenly to obtain the resin composition.

[0095] In a second aspect, the present invention provides a resin film, the material of which comprises the resin composition as described in the first aspect.

[0096] Preferably, the resin film is obtained by coating the resin composition onto a release material and then drying and / or semi-curing it.

[0097] Preferably, the drying and semi-curing temperatures are each independently between 100-180℃, for example, 110℃, 115℃, 120℃, 125℃, 130℃, 135℃, 140℃, 145℃, 150℃, 155℃, 160℃, 165℃, 170℃, or 175℃, as well as specific values ​​between the above points. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific values ​​included in the range.

[0098] Thirdly, the present invention provides a resin-coated copper foil, the resin-coated copper foil comprising a copper foil layer and a resin layer, wherein the material of the resin layer comprises the resin composition as described in the first aspect.

[0099] Preferably, the resin-coated copper foil is obtained by coating the resin composition onto a copper foil and then drying and / or semi-curing it.

[0100] Preferably, the drying and semi-curing temperatures are each independently between 100-180℃, for example, 110℃, 115℃, 120℃, 125℃, 130℃, 135℃, 140℃, 145℃, 150℃, 155℃, 160℃, 165℃, 170℃, or 175℃, as well as specific values ​​between the above points. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific values ​​included in the range.

[0101] Fourthly, the present invention provides a prepreg comprising a substrate and a resin composition as described in the first aspect attached to the substrate.

[0102] Preferably, the resin composition is adhered to the substrate after impregnation and drying.

[0103] Preferably, the raw materials of the substrate include any one or at least two combinations of natural fibers, organic synthetic fibers, organic fabrics, and inorganic fibers; for example, glass fiber cloth, organic fiber cloth, glass fiber paper, quartz glass fiber blended cloth, non-woven fabric, quartz cloth, wood pulp paper, etc.

[0104] Preferably, the fiberglass cloth includes any one or a combination of at least two of Q-fiberglass cloth, E-fiberglass cloth, D-fiberglass cloth, L-fiberglass cloth, M-fiberglass cloth, S-fiberglass cloth, T-fiberglass cloth, and NE-fiberglass cloth.

[0105] Preferably, the organic fiber cloth includes any one or a combination of at least two of polyimide fiber cloth, polyamide fiber cloth, polyester fiber cloth, polyphenylene ether fiber cloth, and liquid crystal polymer fiber cloth.

[0106] For example, the prepreg is prepared by impregnating a substrate with the resin solution of the resin composition and then drying it to obtain the prepreg.

[0107] Preferably, the solvent of the resin adhesive includes any one or a combination of at least two of acetone, butanone, methyl ethyl ketone, cyclohexanone, toluene, and xylene.

[0108] Preferably, the drying temperature is 100-180℃, for example, it can be 110℃, 115℃, 120℃, 125℃, 130℃, 135℃, 140℃, 145℃, 150℃, 155℃, 160℃, 165℃, 170℃ or 175℃, as well as specific values ​​between the above points. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0109] Preferably, the drying time is 1-30 min, for example, it can be 2 min, 5 min, 8 min, 10 min, 15 min, 20 min or 25 min, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0110] Fifthly, the present invention provides a laminate comprising at least one prepreg as described in the fourth aspect.

[0111] In a sixth aspect, the present invention provides a metal foil laminate, the metal foil laminate comprising at least one of the following: a resin film as described in the second aspect, a resin-coated copper foil as described in the third aspect, and a prepreg as described in the fourth aspect.

[0112] Preferably, the metal foil in the metal foil-coated laminate includes any one or a combination of at least two of copper foil, aluminum foil, nickel foil, and alloy foil, with copper foil being more preferred.

[0113] The metal foil is copper foil, and the metal foil laminate is copper clad laminate.

[0114] Preferably, the number of prepreg sheets in the metal foil laminate is 1-20, for example, 2, 3, 5, 7, 9, 10, 11, 13, 15, 17 or 19, and the specific point values ​​between the above point values ​​are not exhaustively listed in this invention due to space limitations and for the sake of brevity.

[0115] For example, the method for preparing the metal foil laminate includes: pressing a metal foil onto one or both sides of a prepreg and curing it to obtain the metal foil laminate; or, stacking at least two prepregs into a laminate, then pressing a metal foil onto one or both sides of the laminate and curing it to obtain the metal foil laminate.

[0116] Preferably, the curing is carried out in a press.

[0117] Preferably, the curing temperature is 170-280℃, such as 180℃, 190℃, 200℃, 210℃, 220℃, 230℃, 240℃, 250℃, 260℃ or 270℃, and specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range, but 200-250℃ is further preferred.

[0118] Preferably, the curing pressure is 10-60 kg / cm². 2 For example, it can be 15kg / cm 2 20kg / cm 2 25kg / cm2 30kg / cm 2 35kg / cm 2 40kg / cm 2 45kg / cm 2 50kg / cm 2 Or 55kg / cm 2 As well as the specific point values ​​between the above point values, due to space limitations and for the sake of brevity, this invention will not exhaustively list the specific point values ​​included in the range.

[0119] Preferably, the curing time is 30-300 min, for example 40 min, 60 min, 80 min, 100 min, 120 min, 150 min, 180 min, 200 min, 220 min, 240 min, 260 min or 280 min, and specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range, but 30-180 min is further preferred.

[0120] In a seventh aspect, the present invention provides a printed circuit board, the printed circuit board comprising at least one of the following: a resin film as described in the second aspect, a resin-coated copper foil as described in the third aspect, a prepreg as described in the fourth aspect, a laminate as described in the fifth aspect, and a metal foil-coated laminate as described in the sixth aspect.

[0121] Compared with the prior art, the present invention has the following beneficial effects:

[0122] (1) In the resin composition provided by the present invention, component A is a specific maleimide-based modifier, which has high heat resistance, high reactivity and low planar thermal expansion coefficient. Component B is a benzocyclobutene resin with a specific structure, which has low dielectric constant and low dielectric loss tangent and high reactivity. By designing and compounding components A and B, the problem of phase separation due to insufficient compatibility between maleimide compounds and low polarity resins is solved, further reducing the warpage of the laminate and the metal-clad laminate at room temperature and after reflow soldering. The resin composition and the metal-clad laminate containing it have high glass transition temperature, low thermal expansion coefficient, low dielectric constant and low dielectric loss tangent, which fully meet the performance requirements of high-speed packaging substrate materials.

[0123] (2) Through the component design and optimization of the resin composition, the resin composition has no compatibility problems such as resin agglomeration and precipitation. The metal foil laminate prepared by impregnating glass fiber cloth with the resin composition in the clear state has a dielectric constant Dk≤3.7, dielectric loss tangent Df≤0.004, thermal expansion coefficient XY-CTE≤10ppm / ℃, glass transition temperature Tg of 220-260℃, and Δ warpage ≤57μm after reflow soldering and at room temperature. It has excellent dielectric properties, heat resistance and deformation resistance, and fully meets the performance requirements of high-speed packaging substrate materials. Attached Figure Description

[0124] Figure 1 Infrared spectrum of benzocyclobutene resin A-BCBS1 provided in Example 1;

[0125] Figure 2 Infrared spectrum of benzocyclobutene resin B-BCB2 provided in Preparation Example 4;

[0126] Figure 3 GPC spectrum of benzocyclobutene resin B-BCB2 provided in Example 4. Detailed Implementation

[0127] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.

[0128] In one specific embodiment, the benzocyclobutene resin is a type A benzocyclobutene resin, wherein the first structural unit of the type A benzocyclobutene resin has a structure as shown in formula IA and / or formula IB, and is formed by using a butadiene-based polymer and a benzocyclobutene monomer ( It is abbreviated as BCBS and is obtained by reacting in the presence of organic peroxides.

[0129] In another specific embodiment, the benzocyclobutene resin is a type B benzocyclobutene resin, wherein the first structural unit of the type B benzocyclobutene resin has a structure as shown in Formula C1, and is made by using a butadiene-based polymer and 4-bromobenzocyclobutene. It is obtained by coupling reaction in the presence of palladium catalysis system.

[0130] The butadiene-based polymer used in the aforementioned method is specifically as follows:

[0131] B2000, polybutadiene, a structural unit formed by 1,2-polymerization ( (The same below) has a molar percentage content of 88%, Nippon Soda Co., Ltd.;

[0132] B3000, polybutadiene, 92% molar percentage of structural units formed by 1,2-polymerization, Nippon Soda Co., Ltd.

[0133] BI3060, partially hydrogenated polybutadiene, with a molar percentage of 60% of structural units formed by 1,2-polymerization, Nippon Soda Co., Ltd.

[0134] Ricon 184, a butadiene-styrene copolymer (styrene-butadiene resin), has a 30% molar percentage of styrene structural units formed by 1,2-polymerization. The molar percentage content is 22%, from Sartomer, Inc., USA.

[0135] The preparation method of the benzocyclobutene resin in this invention is described in detail below through preparation examples:

[0136] Preparation Example 1

[0137] A benzocyclobutene resin A-BCBS1 is prepared by the following method:

[0138] Weigh 50g of polybutadiene B3000, 50g of BCBS, and 80mL of toluene into a flask and dissolve them into a homogeneous solution. Heat the solution to reflux temperature under an argon atmosphere. Dissolve 0.5g of tert-butylisopropylphenyl peroxide (BIPB) in 20mL of toluene, and then add it dropwise over 40 minutes. React at the reflux temperature of toluene. Monitor the reaction by TLC (thin-layer chromatography) until the BCBS starting material spot disappears. Stop the reaction and cool to obtain benzocyclobutene resin A-BCBS1, which can be used without separation.

[0139] Preparation Examples 2-3

[0140] A benzocyclobutene resin differs from Preparation Example 1 in that the types and amounts of raw materials used are different, as shown in Table 1; the process parameters not shown in Table 1 are the same as those in Preparation Example 1.

[0141] Table 1

[0142]

[0143] In Preparation Examples 1-3, the structure of the benzocyclobutene resin was characterized and confirmed using Fourier transform infrared spectroscopy (FTIR, IS10FT-IR, Thermo Fisher Scientific). The infrared spectrum of benzocyclobutene resin A-BCBS1 provided in Preparation Example 1 is shown below. Figure 1 As shown, from Figure 1 From this, we can know that it is 1473cm -1The characteristic absorption at this point, attributed to the four-membered ring of benzocyclobutene, indicates the presence of a benzocyclobutene structure in A-BCBS1. The TLC column showed the disappearance of the starting material, indicating that benzocyclobutene has been incorporated into polybutadiene. At 1495 cm⁻¹ -1 The presence of absorption in non-aromatic cyclic structures indicates the presence of double bonds forming a ring in polybutadiene; however, at 905 cm⁻¹... -1 and 995cm -1 The strong absorption of the end double bonds indicates that the polybutadiene structure is a partial polymerization.

[0144] As shown in Table 1, the first structural unit (%) represents the mass percentage of the first structural unit (formula IA and / or formula IB) containing benzocyclobutene groups in the side chain in the benzocyclobutene resin, which is calculated by the amount of BCBS fed and the mass of the butadiene-based polymer (since thin-layer chromatography is used for detection during the preparation process to ensure that the BCBS reaction is complete, the BCBS is completely converted into the first structural unit).

[0145] Preparation Example 4

[0146] A benzocyclobutene resin B-BCB1 is prepared by the following method:

[0147] 169.44 g of 4-bromobenzocyclobutene (4-bromoBCB), 100 g of polybutadiene B2000, 16.35 g of tris(o-methylphenyl)phosphine, 7.48 g of palladium acetate, 500 g of triethylamine, and 1000 g of acetonitrile were added to a flask and stirred at 85 °C for 24 h under an argon atmosphere. The mixture was cooled, and the solvent was evaporated to dryness. The solution was rapidly passed through a column using neutral alumina, and the solvent was evaporated to dryness to obtain a viscous liquid. After dissolving the liquid in toluene, four times the volume of toluene in methanol was added, and the mixture was thoroughly shaken and allowed to stand. The toluene layer was then separated. The solution was then concentrated by rotary evaporation and vacuum dried to obtain a colorless viscous liquid, namely benzocyclobutene resin B-BCB1.

[0148] Preparation Examples 5-6

[0149] A benzocyclobutene resin differs from Preparation Example 4 in that the types and amounts of raw materials used are different, as shown in Table 2; the process parameters not shown in Table 2 are the same as those in Preparation Example 4.

[0150] Table 2

[0151]

[0152] In Preparation Examples 4-6, the structure of the benzocyclobutene resin was characterized and confirmed using Fourier transform infrared spectroscopy (FTIR, IS10FT-IR, Thermo Fisher Scientific). The infrared spectrum of benzocyclobutene resin B-BCB1 in Preparation Example 4 is shown below. Figure 2 As shown, from Figure 2 From this, we can know that it is 1473cm-1 The characteristic absorption at the point of origin is attributed to the four-membered ring of benzocyclobutene, indicating the presence of a benzocyclobutene structure in the B-BCB1 resin. The TLC column shows the disappearance of the raw material, indicating that benzocyclobutene has been incorporated into polybutadiene.

[0153] According to GB / T 21863-2008, based on polystyrene calibration, the molecular weight of benzocyclobutene resin CH-BCB1 was determined by gel permeation chromatography (GPC). The resulting GPC spectrum is shown below. Figure 3 As shown, Figure 3 The 3241 shown is the viscosity-average molecular weight of benzocyclobutene resin B-BCB1, and its number-average molecular weight Mn is 2416.

[0154] In Table 2, the first structural unit (%), second structural unit (%), and third structural unit (%) represent the molar percentages of the first structural unit (Formula IC), second structural unit (Formula II), and third structural unit (Formula IIIA and / or Formula IIIB) containing benzocyclobutene groups in the side chain, respectively, in the benzocyclobutene resin. The first structural unit (%) and second structural unit (%) were calculated based on the amount of 4-bromoBCB fed and the molar percentage of the 1,2-polymerized structural units in the resin raw material (since thin-layer chromatography was used for detection during the preparation process to ensure the complete reaction of 4-bromoBCB). Therefore, 4-bromoBCB is completely converted into the first structural unit. The difference in molar percentage between the 1,2-polymerized structural unit and the first structural unit in the resin raw material is the amount of the second structural unit (corresponding to polybutadiene as the resin raw material). If the resin raw material is butadiene-styrene copolymer, the molar percentage of the second structural unit is the difference in molar percentage between the 1,2-polymerized structural unit and the first structural unit in the resin raw material plus the molar percentage of the styrene structural unit. The third structural unit comes from the resin raw material (polybutadiene or butadiene-styrene copolymer) and is obtained from the raw material manufacturer.

[0155] Preparation Example 7

[0156] The addition reaction product of maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and amine compound a2 containing at least two primary amino groups in one molecule, hereinafter referred to as BMI-A1, is prepared as follows:

[0157] In a three-necked flask equipped with a thermometer, a stirrer, and a reflux condenser, 1 part by weight of the amine compound Kayahard AA (3,3'-diethyl-4,4'-diaminodiphenylmethane, Nippon Kayaku Co., Ltd.), 9 parts by weight of X-22-161A (a siloxane compound with two primary amino groups at the molecular end, Shin-Etsu Chemical Co., Ltd.), 30 parts by weight of the maleimide compound BMI-4000 (2,2-bis(4-(4-maleiminophenoxy)phenyl)propane, Yamato Kasei Corporation), and 30 parts by weight of the solvent propylene glycol monomethyl ether were added. The mixture was reacted at 115°C for 360 min to obtain BMI-A1.

[0158] Preparation Example 8

[0159] Nine parts by weight of X-22-161B (a siloxane compound with two primary amino groups at the molecular end, Shin-Etsu Chemical Co., Ltd.), 31 parts by weight of maleimide compound BMI-1000 (bis(4-maleimide-phenyl)methane, Yamato Chemical Co., Ltd.), and 30 parts by weight of solvent propylene glycol monomethyl ether were added to a three-necked flask equipped with a thermometer, a stirrer, and a reflux condenser. The mixture was reacted at 115°C for 360 min to obtain BMI-A2.

[0160] In the following specific embodiments of the present invention, the materials involved are as follows:

[0161] 1. Component A: The addition reaction product of maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and amine compound a2 containing at least two primary amino groups in one molecule.

[0162] BMI-A1, Preparation Example 7;

[0163] BMI-A2, Preparation Example 8.

[0164] 2. Component B: Benzocyclobutene resin

[0165] The benzocyclobutene resins A-BCBS1 to A-BCBS3 provided in Examples 1-3 were prepared.

[0166] Benzocyclobutene resins B-BCB1 to B-BCB3 were prepared according to Examples 4-6.

[0167] 3. Component B': Benzocyclobutene resin

[0168] CYCLOTENE3022, a benzocyclobutene resin containing siloxane groups in its molecular backbone, manufactured by Dow Chemical Company, has the following structure:

[0169]

[0170] 4. Component C

[0171] OPE-2st 1200, polyphenylene ether containing vinyl benzyl groups at the end, Mitsubishi Chemical Corporation.

[0172] 5. Thermoplastic polymers

[0173] Tuftec M1913, a hydrogenated styrene-butadiene copolymer with maleic anhydride structural units, Asahi Kasei Chemicals Co., Ltd.

[0174] 6. Inorganic fillers

[0175] SC2500-SXJ, spherical silica modified with aniline-siloxane, average particle size D 50 It is 0.5μm, from Admatechs Co., Ltd., Japan.

[0176] 7. Coupling agents

[0177] KBM-573, phenylaminosilane coupling agent, Shin-Etsu Chemical Industry Co., Ltd.

[0178] Examples 1-10, Comparative Examples 1-5

[0179] A resin composition, the types and amounts of each component are shown in Tables 3, 4 and 5, and the unit of amount of each component is "parts".

[0180] A prepreg comprising the resin composition and a metal foil-coated laminate are prepared by the following method:

[0181] (1) Mix and disperse each component of the resin composition with toluene solvent according to the formula amount to prepare a resin solution with a solid content of 65%.

[0182] (2) Impregnate the glass fiber cloth (3313L glass fiber cloth manufactured by Hubel in Taiwan, China) with the resin solution, and then heat and dry it in a forced-air oven at 130°C for 4 minutes to transform the resin composition in the varnish state into a semi-cured resin composition. The average thickness is controlled to be 100μm to obtain the prepreg.

[0183] (3) Stack two (or eight) sheets of prepreg obtained in step (2) together, and press a 12μm thick low-profile electrolytic copper foil onto the top and bottom sides of the stack. Then press the stack at 220℃ and 45kg / cm² in a press. 2 After curing for 2 hours, a metal foil laminate with a core board thickness of 0.20 mm (or 0.80 mm) is obtained. After etching the copper foil of the metal foil laminate, a laminate with a thickness of 0.20 mm (or 0.80 mm) is obtained.

[0184] The performance of the metal foil-coated laminate / laminate is tested using the following specific methods:

[0185] (1) Glass transition temperature Tg: A laminate with a length of 60 mm, a width of 10 mm, and a thickness of 0.80 mm was used as a sample and measured using a dynamic mechanical thermal analyzer (DMA) at a heating rate of 10 °C / min. The result was taken as the transition peak temperature of tanδ, in °C.

[0186] (2) Planar thermal expansion coefficient XY-CTE: A laminate with a length of 60 mm, a width of 4 mm, and a thickness of 0.20 mm was used as the sample. The glass fiber warp direction was Y-direction, and the glass fiber weft direction was X-direction. The sample was dried in an oven at 105℃ for 1 h and then cooled to room temperature in a desiccator. The mechanical thermal analysis (TMA) method was used for measurement. The heating rate was 10℃ / min. The temperature was increased from room temperature to 200℃ twice. After the first heating was completed and the sample was cooled to room temperature, it was placed again for the second heating. The result was the planar thermal expansion coefficient at the second heating from 60℃ to 120℃, and the unit was ppm / ℃.

[0187] (3) Dielectric constant Dk and dielectric loss tangent Df: A laminate with a length of 100 mm, a width of 100 mm, and a thickness of 0.20 mm was used as a sample. After the sample was ultrasonically cleaned in deionized water to remove impurities on the surface, it was dried in an oven at 105℃ for 1 h and then cooled to room temperature in a desiccator. The dielectric constant (Dk) and dielectric loss tangent (Df) at a frequency of 10 GHz were measured using a cavity resonator.

[0188] (4) Compatibility assessment: Prepare resin compositions in clear varnish state according to Tables 3-5 (without inorganic fillers), place them in a 40mL measuring cylinder. If the resin composition in clear varnish state is observed to be turbid, it is judged as "incompatible"; if the resin composition in clear varnish state is observed to be clear, seal and let stand for 1 day, and observe the resin phase separation after 1 day. If the resin separates into phases and one phase is rubbery, it is judged as "incompatible"; otherwise, it is judged as "compatible".

[0189] (5) Room temperature and post-reflow warpage: A laminate with a length of 240 mm, a width of 70 mm, and a thickness of 0.20 mm was used as a sample. The warpage was measured using a warpage tester, with the unit being μm. The warpage size at 30°C before reflow soldering was recorded as "room temperature warpage", and the warpage at 30°C after reflow soldering was recorded as "post-reflow soldering warpage".

[0190] Δwarping = Post-reflow warping - Room temperature warping;

[0191] The reflow soldering parameters were set as follows: temperature rise from 30℃ to 260℃, then temperature drop from 260℃ to 30℃, at a rate of 3℃ / min.

[0192] The test results are shown in Tables 3, 4 and 5.

[0193] Table 3

[0194]

[0195]

[0196] Table 4

[0197]

[0198]

[0199] Table 5

[0200]

[0201]

[0202] Based on the performance test data in Tables 3-4 above, it can be seen that the resin compositions provided in Examples 1-10 of this invention have no compatibility issues such as resin agglomeration and precipitation. The metal foil laminate prepared by impregnating glass fiber cloth with the resin composition in the clear state has a dielectric constant Dk≤3.7, dielectric loss tangent Df≤0.004, coefficient of thermal expansion XY-CTE≤10ppm / ℃, and glass transition temperature Tg of 220-260℃. It has a high glass transition temperature, low coefficient of thermal expansion, and excellent dielectric properties. In particular, the warpage at room temperature and after reflow soldering is low. The Δ warpage after reflow soldering and at room temperature is ≤57μm, which has excellent resistance to deformation and fully meets the performance requirements of high-speed packaging substrate materials.

[0203] According to the performance test data in Table 5, when the resin composition lacks component B (Comparative Example 1), and a thermoplastic polymer is added to obtain low dielectric loss, the resin composition in the clear varnish state becomes cloudy, separates into phases after standing, exhibits poor resin compatibility, and suffers from poor resistance to deformation due to insufficient crosslinking density, resulting in significant warpage at room temperature and after reflow soldering. When the content of component A in the resin composition is too high (Comparative Example 2), the dielectric loss tangent of the laminate is too large, failing to meet the requirements for low dielectric loss in high-speed substrate materials. When the content of component B in the resin composition is too high (Comparative Example 3), the laminate... An increase in the coefficient of thermal expansion and a decrease in the glass transition temperature result in a decrease in resistance to deformation, failing to meet the requirements for low thermal deformation of the substrate material. When the structure of component B in the resin composition does not contain the first and second structural units of the present invention (Comparative Example 4), the coefficient of thermal expansion of the laminate increases, the glass transition temperature decreases, resulting in a decrease in resistance to deformation, failing to meet the requirements for low warpage of the substrate material. When component A is absent from the resin composition (Comparative Example 5), the glass transition temperature of the laminate decreases, the heat resistance decreases, the coefficient of thermal expansion increases, the resistance to deformation decreases, and warpage is significant.

[0204] The applicant declares that the present invention is illustrated through the above embodiments with respect to the resin composition and the prepreg, laminate, and metal foil-coated laminate containing the resin composition. However, the present invention is not limited to the above process steps, i.e., it does not mean that the present invention must rely on the above process steps to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the raw materials used in the present invention, additions of auxiliary components, and selection of specific methods all fall within the protection and disclosure scope of the present invention.

Claims

1. A resin composition, characterized in that, The resin composition comprises the following components in parts by weight: Component A 50-90 parts Component B5-60 parts; The component A includes an addition reaction product of a maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and an amine compound a2 containing at least two primary amino groups in one molecule; Component B is a benzocyclobutene resin, which contains at least one first structural unit and at least one second structural unit. The first structural unit has a structure as shown in at least one of formulas IA, IB, and IC: Formula IA; Formula IB; Formula IC; wherein R1 is vinylidene or ethylidene; The second structural unit has the structure shown in Equation II: Formula II; Wherein, R2 is vinyl, ethyl, or phenyl; The molar percentage of the first structural unit in the benzocyclobutene resin is 30-60%; The molar percentage of the second structural unit in the benzocyclobutene resin is 30-90%.

2. The resin composition according to claim 1, characterized in that, The benzocyclobutene resin further comprises a third structural unit having a structure as shown in Formula IIIA and / or Formula IIIB: Formula IIIA; Formula IIIB.

3. The resin composition according to claim 2, characterized in that, The molar percentage of the third structural unit in the benzocyclobutene resin is ≤40%.

4. The resin composition according to claim 3, characterized in that, The molar percentage of the third structural unit in the benzocyclobutene resin is ≤30%.

5. The resin composition according to claim 4, characterized in that, The molar percentage of the third structural unit in the benzocyclobutene resin is ≤20%.

6. The resin composition according to claim 1, characterized in that, The number average molecular weight of the benzocyclobutene resin is 1,000-200,000.

7. The resin composition according to claim 1, characterized in that, The maleimide compound a1 contains two N-substituted maleimide groups in one molecule.

8. The resin composition according to claim 7, characterized in that, The maleimide compound a1 includes N,N'-ethylidene bismaleimide, N,N'-hexamethylene bismaleimide, N,N'-(1,3-phenylene)bismaleimide, N,N'-(1,3-(2-methylphenylene))bismaleimide, N,N'-(1,3-(4-methylphenylene))bismaleimide, N,N'-(1,4-phenylene)bismaleimide, bis(4-maleimide-phenyl)methane, bis(3-methyl-4-maleimide-phenyl)methane, bis(3,5-dimethyl-4-maleimide-phenyl)methane, bis(3- Ethyl-5-methyl-4-maleimidephenyl)methane, bis(3-ethyl-4-maleimidephenyl)methane, bis(3,5-diethyl-4-maleimidephenyl)methane, bis(4-maleimidephenyl) ether, bis(4-maleimidephenyl) ketone, bis(4-maleimidecyclohexyl)methane, 1,4-bis(4-maleimidephenyl)cyclohexane, 1,4-bis(maleimidemethyl)cyclohexane, 1,4-bis(maleimidemethyl)benzene, 1,3-bis(4-maleimidephenoxy)benzene, 1,3-bis(3-maleimidephenyl)benzene 1,1-bis(4-(3-maleiminophenoxy)phenyl)methane, 1,1-bis(4-(4-maleiminophenoxy)phenyl)ethane, 1,1-bis(4-(3-maleiminophenoxy)phenyl)ethane, 1,2-bis(4-(3-maleiminophenoxy)phenyl)ethane, 1,2-bis(4-(4-maleiminophenoxy)phenyl)ethane, 2,2-bis(4-(3-maleiminophenoxy)phenyl)propane, 2,2-bis(4-(4-maleiminophenoxy)phenyl)propane 2,2-Bis(4-(3-maleimide phenoxy)phenyl)butane, 2,2-bis(4-(4-maleimide phenoxy)phenyl)butane, 4,4'-bis(3-maleimide phenoxy)biphenyl, 4,4'-bis(4-maleimide phenoxy)biphenyl, bis(4-(3-maleimide phenoxy)phenyl)one, bis(4-(4-maleimide phenoxy)phenyl)one, bis(4-(3-maleimide phenoxy)phenyl)ether, bis(4-(4-maleimide phenoxy)phenyl)ether, any one or a combination of at least two of the following:

9. The resin composition according to claim 8, characterized in that, The maleimide compound a1 includes any one or a combination of at least two of bis(3-ethyl-5-methyl-4-maleimide-phenyl)methane, bis(4-maleimide-phenyl)methane, and 2,2-bis(4-(4-maleimide-phenoxy)phenyl)propane.

10. The resin composition according to claim 1, characterized in that, The amine compound a2 includes siloxane compounds containing at least two primary amino groups, diaminobenzidine, 3,3'-dimethoxy-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminobiphenyl, 3,3'-diethyl-4,4'-diaminobiphenyl, diaminodiphenylmethane, 3,3'-dimethoxy-4,4'-diaminodiphenylmethane, and 3,3'-dimethyl-4,4'-diaminodiphenylmethane. 3,3'-dimethyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-diethyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, diaminodiphenyl ether, 3,3'-dimethoxy-4,4'-di... Amino diphenyl ether, 3,3'-dimethyl-4,4'-diamino diphenyl ether, 3,3'-dimethyl-5,5'-dimethyl-4,4'-diamino diphenyl ether, 3,3'-diethyl-4,4'-diamino diphenyl ether, 3,3'-diethyl-5,5'-diethyl-4,4'-diamino diphenyl ether, 3,3'-dimethyl-5,5'-diethyl-4,4'-diamino diphenyl ether, 1,3 - any one or a combination of at least two of the following: bis(4-aminophenoxy)benzene, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 2,2-bis(4-(3-aminophenoxy)phenyl)propane, 4,4'-bis(4-aminophenoxy)biphenyl, 1,4-bis(4-aminophenoxy)benzene, 2,2'-dimethyl-4,4'-diaminobiphenyl, and 4,4'-diamino-3,3'-dihydroxybiphenyl.

11. The resin composition according to claim 10, characterized in that, The amine compound a2 includes any one or a combination of at least two of the following: a siloxane compound containing at least two primary amino groups; 3,3'-dimethyl-4,4'-diaminodiphenylmethane; 3,3'-dimethyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane; 3,3'-diethyl-4,4'-diaminodiphenylmethane; 3,3'-diethyl-5,5'-diethyl-4,4'-diaminodiphenylmethane; 3,3'-dimethyl-5,5'-diethyl-4,4'-diaminodiphenylmethane; and 2,2-bis(4-(4-aminophenoxy)phenyl)propane.

12. The resin composition according to claim 1, characterized in that, The resin composition further comprises 1-50 parts by weight of component C, wherein component C includes any one or a combination of at least two of epoxy resin, acid anhydride compound, active ester compound, and compound having carbon-carbon unsaturated double bonds in its molecule.

13. The resin composition according to claim 12, characterized in that, Component C includes compounds having intramolecular carbon-carbon unsaturated double bonds.

14. The resin composition according to claim 13, characterized in that, The compounds having carbon-carbon unsaturated double bonds within their molecules include any one or a combination of at least two of the following: unsaturated polyphenylene ethers, polyfunctional vinyl compounds, allyl compounds, acrylate compounds, acenaphthene compounds, and polybutadiene.

15. The resin composition according to claim 1, characterized in that, The resin composition further includes 5-30 parts by weight of thermoplastic polymer.

16. The resin composition according to claim 15, characterized in that, The thermoplastic polymer includes any one or a combination of at least two of styrene-based polymers, hydrogenated styrene-based polymers, and polyolefin resins.

17. The resin composition according to claim 1, characterized in that, The resin composition further includes 0.01-5 parts by weight of a curing accelerator.

18. The resin composition according to claim 17, characterized in that, The curing accelerator includes any one or a combination of at least two of the following: acidic curing accelerators, organophosphorus curing accelerators, imidazole curing accelerators, pyridine curing accelerators, amine curing accelerators, peroxides, and organometallic salts.

19. The resin composition according to claim 1, characterized in that, The resin composition further includes 5-250 parts by weight of inorganic filler.

20. The resin composition according to claim 1, characterized in that, The resin composition further includes 0.01-10 parts by weight of coupling agent.

21. The resin composition according to claim 20, characterized in that, The coupling agent includes a silane coupling agent.

22. A resin film, characterized in that, The resin film is made of the resin composition as described in any one of claims 1-21.

23. The resin film according to claim 22, characterized in that, The resin film is obtained by coating the resin composition onto a release material and then drying and / or semi-curing it.

24. A resin-coated copper foil, characterized in that, The resin-coated copper foil comprises a copper foil layer and a resin layer, wherein the material of the resin layer comprises the resin composition as described in any one of claims 1-21.

25. A prepreg, characterized in that, The prepreg comprises a substrate and a resin composition as described in any one of claims 1-21 attached to the substrate.

26. The prepreg according to claim 25, characterized in that, The resin composition is adhered to the substrate after impregnation and drying.

27. A laminate, characterized in that, The laminate comprises at least one sheet of prepreg as described in claim 25 or 26.

28. A metal foil-coated laminate, characterized in that, The metal foil laminate includes at least one of the following: the resin film as described in claim 22 or 23, the resin-coated copper foil as described in claim 24, and the prepreg as described in claim 25 or 26.

29. A printed circuit board, characterized in that, The printed circuit board includes at least one of the following: the resin film as described in claim 22 or 23, the resin-coated copper foil as described in claim 24, the prepreg as described in claim 25 or 26, the laminate as described in claim 27, and the metal foil-coated laminate as described in claim 28.

Citation Information

Patent Citations

  • Thermosetting resin composition, prepreg comprising same, metal-foil-coated laminate and printed circuit board

    CN109825081A

  • High-thermal-conductivity hydrocarbon resin-based prepreg and high-frequency copper-clad plate prepared from same

    CN114437435A

  • Resin for high-frequency and high-speed copper-clad plate and polymerization method thereof

    CN115677940A

  • Resin composition, prepreg and metal foil-clad laminated board

    CN116410594A

  • Resin composition

    JP2022013142A